Nutritional pathway for people with motor neurone disease. - Marsden, R; Allan, P; Blackwell, V; East, J; Lawson, C; Nickol, A; Millard, E; Talbot, K; Thompson, A; Turner, M (Mark Allen Healthcare, 2016)
This paper provides an overview of the nutritional management and care of people living with motor neurone disease (MND) in a specialist nutrition clinic. A specialist pathway of care has been developed to enable people living with MND to undergo a percutaneous endoscopic gastrostomy (PEG) procedure in a safe way; the pathway incorporates attendance at a dedicated nutrition clinic, a stratification tool to identify patients with a high periprocedural risk and a PEG insertion team with significant experience in the MND population. Since this pathway has been in place, gastrostomies have been successfully placed in patients with a forced vital capacity (FVC) of less than 50%; previously, this would not have been possible.